Learning Adobe Audition CC - Sengstack, Jeff (InfiniteSkills, 2013)
"In this Adobe Audition CC training course from expert author Jeff Sengstack, you will learn how to import, edit and clean audio using the tools and techniques this software has included. Audition CC adds new features that makes editing your audio easier and faster than ever before! This tutorial is designed for the beginner, and no previous Audition experience is required. Jeff takes you through Audition CC step by step, with each lesson building on the one previous. You are not overwhelmed with information, Jeff teaches you each operation as he does it, making the concepts and tools easy to understand and absorb. Some of the topics that are covered in this Adobe Audition video training are; understanding the Audition workflow, importing and recording audio, editing audio, adding audio effects, working with noise reduction and restoration effects, using diagnostic tools, stretching time, changing pitch, building multitrack sessions, and of course, saving and exporting your finished product. Once you have completed this Audition CC video tutorial, you will have the confidence and skills you need to import, edit, clean and export high-quality audio projects. Working files are included, allowing you to follow along with the author throughout the lessons."--Resource description page.